2007
DOI: 10.1038/sj.onc.1210706
|View full text |Cite|
|
Sign up to set email alerts
|

Protein kinase WNK2 inhibits cell proliferation by negatively modulating the activation of MEK1/ERK1/2

Abstract: The recently identified subfamily of WNK protein kinases is characterized by a unique sequence variation in the catalytic domain and four related human WNK genes were identified. Here, we describe the cloning and functional analysis of the human family member WNK2. We show that the depletion of endogenous WNK2 expression by RNA interference in human cervical HeLa cancer cells led to the activation of the extracellular signal-regulated kinase (ERK)1/2 mitogen-activated protein kinases but, in contrast to the de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
59
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 73 publications
(62 citation statements)
references
References 45 publications
2
59
1
Order By: Relevance
“…The degree of ERK1/2 activation and subsequent G1/S cell cycle progression that was observed following MCLR treatment is comparable to that described for other tumorigenic stimuli (Moniz et al, 2007;Moniz and Peter, 2010) and thus biologically meaningful. Considering that the ERK1/2 pathway is known to be upregulated in approximately one-third of all human cancers (Dhillon et al, 2007), our results emphasise the importance to confirm in vivo the impact of MCLR on tumour promotion at kidney level.…”
Section: Discussionsupporting
confidence: 51%
“…The degree of ERK1/2 activation and subsequent G1/S cell cycle progression that was observed following MCLR treatment is comparable to that described for other tumorigenic stimuli (Moniz et al, 2007;Moniz and Peter, 2010) and thus biologically meaningful. Considering that the ERK1/2 pathway is known to be upregulated in approximately one-third of all human cancers (Dhillon et al, 2007), our results emphasise the importance to confirm in vivo the impact of MCLR on tumour promotion at kidney level.…”
Section: Discussionsupporting
confidence: 51%
“…32 WNK2 reduces cell proliferation by inhibiting the MEK1/ERK1/2 signaling pathway. 36 We previously showed that WNK4 overexpression enhances ERK1/2 phosphorylation. 37 In the present study, we found that overexpression of WNK1 decreased ERK1/2 phosphorylation, whereas knockdown of WNK1 expression using an siRNA technique enhanced ERK1/2 phosphorylation.…”
Section: Discussionmentioning
confidence: 99%
“…Other reports have suggested that WNK isoforms regulate proliferation and apoptosis, perhaps through caspase 3 (Moniz et al, 2007;Verissimo et al, 2006). Furthermore, in the majority of infiltrative gliomas WNK2 expression was reportedly silenced by methylation, and deletions within the WNK2 gene were found at low frequency (Hong et al, 2007).…”
Section: Other Wnk-regulated Pathwaysmentioning
confidence: 99%